Associations of high altitude polycythemia with polymorphisms in EPHA2 and AGT in Chinese Han and Tibetan populations - Liu, Lijun; Zhang, Yao; Zhang, Zhiying; Zhao, Yiduo; Fan, Xiaowei; Ma, Lifeng; Zhang, Yuan; He, Haijin; Kang, Longli (Oncotarget, 2017)
High altitude polycythemia (HAPC) refers to the long-term living in the plateau of the hypoxia environment is not accustomed to cause red blood cell hyperplasia. The pathological changes are mainly the various organs and tissue congestion, blood stasis and hypoxia damage. Although chronic hypoxia is the main cause of HAPC, the related molecular mechanisms remain largely unclear. This study aims to explore the genetic basis of HAPC in the Chinese Han and Tibetan populations. We enrolled 100 patients (70 Han, 30 Tibetan) with HAPC and 100 healthy control subjects (30 Han, 70 Tibetan). To explore the hereditary basis of HAPC and investigate the association between with and HAPC in Chinese Han and Tibetan populations. Using the Chi-squared test and analyses of genetic models, rs2291804, rs2291805, rs3768294, rs3754334, rs6603856, rs6669624, rs11260742, rs13375644 and rs10907223 in , and rs699, rs4762 and rs5051 in showed associations with reduced HAPC susceptibility in Han populations. Additionally, in Tibetan populations, rs2478523 in showed an increased the risk of HAPC. Our study suggest that polymorphisms in the and correlate with susceptibility to HAPC in Chinese Han and Tibetan populations.